The Effect Of Using Personal Protection Equipment (PPE), Mileage, And Smoking Habits On Hair Lead (Pb) Levels: Pengaruh Penggunaan Alat Pelindung Diri (APD), Jarak Tempuh Dan Kebiasaan Merokok Terhadap Kadar Timbal (Pb) Rambut - Wulandari, Devyana Dyah; Rohmah, Wardah; Nidianti, Ersalina; Santoso, Andreas Putro Ragil; Andini, Ary (Universitas Muhammadiyah Sidoarjo, 2021)
Street sweepers, traffic officers, roadside sellers and motorcyclists, including students are subjects who are vulnerable to exposure to vehicle fumes. One of the air pollution generated from motor vehicle fumes is lead (Pb) which is toxic to humans and is accumulative. This study aimed to analyze the relationship between characteristic factors and lead levels in hair using the Atomic Absorption Spectroscopy (AAS) method. Respondents in this study were 32 male university students. The results showed a significance value of 0.274 (p> 0.05) on the parameter of PPE use, 0.049 (p <0.05) on the mileage parameter, and 0.576 (p> 0.05) on the smoking habit parameter. So it can be concluded that there is no effect of the use of PPE and smoking habits on hair lead levels and there is an effect of mileage on hair lead levels in student respondents.